KUALITAS PELAYANAN WAITERS DI GRAND ZURI HOTEL DUMAI - Sinta Deswanti; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Hospitality is one of the important components that can support the development of theworld of tourism. The Hospitality Industry is one of the industries that play animportant role in the economic development and the world of tourism in Indonesia.service is any action or desire which may be offered by one party to another, essentiallyintangible and does not result in any ownership. And a sense of fun given to others whoaccompanied hospitality and ease in meeting the needs of consumers.This research was conducted in Grand Zuri Kota Dumai.Jl Jend. Sudirman No. 88,Dumai City, Bintan Village, Dumai City District, Dumai City. This hotel is chosen as aplace of research because in it has the quality of service that visitors need when visitingthis hotel.This study aims to determine the response of visitors to the quality of service at theGrand Hotel Zuri Dumai City. This research uses quantitative descriptive method toprocess the data obtained in the field through interviews, all the information collectedand studied to become a unified whole (Kusuma and Sugono 2000). As for the sample inresearch sebanyan 100 respondents, data collection techniques used are observations,interviews, questionnaires, using Likert scale as a measuring tool. Based on the resultsof research that has been done quality service with variable Reliability,Responsivensse, Assurance Empathy and Tangible with good research conclusions.Keywords :Realibility, Responsivinsse, Assurance, Empathy, Tangible, HotelGrand Zuri